Notes sobre l'ordenament lingüístic d'una Catalunya sobirana. Quin model? Quin procés? - Isidor Marí (Revista d'Estudis Autonòmics i Federals, 2015)
The definition of the legal language framework in a hypothetical sovereign Catalonia is not primarily a theoretical exercise or the expression of a particular political position. In order to achieve a satisfactory arrangement for a multilingual Catalonia in a context of sovereignty, the political process and the social legitimation of this future linguistic regime should be taken into account. The identification of the majority of the society with the political project of sovereignty depends on linguistic factors which are inseparable from other collective aspirations. Along the different stages of the process (initial situation, access to sovereignty, constitutional process and the new institutional and legal framework), there is a number of factors that can have a great influence upon the process itself such as the sociolinguistic composition of the population, as the equitable management of diversity, as the idea of citizenship, and as a approach to multilingualism. It is from these factors that we must foresee the eventual official status of languages and its institutional and legal framework. Decisions on the official status which is attributed to languages involve socio-political responsibilities that cannot be overlooked if one aims to ensure both the identification of a majority with the aims pursued by sovereignty and the full recovery of Catalan and Aranese Occitan as heritage languages of Catalonia.